Reform of Patent Regulations in Indonesia - Kusumaningrum, Rindia Fanny (Law Research Review Quarterly, 2016)
Patent protection especially in Indonesia needs special attention from the Government because the patent itself is related to the field of technology which is rapidly changing and evolving in accordance with the ever-changing science and the changing conditions of society due to technological developments. This brings consequences with the development of technology, people are required to think more creatively or have creative ideas of innovation to be able to create an appropriate technology that can certainly benefit the entire community and can compete with other developing countries.